Patch test results with rubber series in the European Surveillance System on Contact Allergies (ESSCA), 2013/14 - Uter, Wolfgang; Weisshaar, Elke (Contact dermatitis, 2016)
Background. Contact: allergy to rubber additives is common, particularly in patients with occupational dermatitis. Objectives: to descriptively analyse and compare patch test reactions in patients patch tested both with the baseline series and with an additional ‘rubber series’ as used in the department. Methods: patch test data from those members of the European Surveillance System on Contact Allergies (ESSCA) network (www.essca-dc.org) who also contributed data on rubber series patch test results were retrospectively analysed. Results: among 29 522 patients patch tested, 2870 were eligible, that is, patch tested both with the baseline series and with a special rubber series. Of these, 8.8% had positive reaction(s) to one of the baseline screening rubber allergens (as compared with 4.2% in all patients), most often to carba mix, 12.3% had positive reaction(s) to allergens from an additional rubber series, and 6.4% had positive reaction(s) to both. Conclusions: additional testing with a dedicated rubber series, containing break-down single ingredients of mixes from the baseline series and additional rubber allergens, is warranted in patients with suspected contact allergy to rubber, to avoid false-negative results.
Gesehen am 28.11.2017